Tailoring BiOBr Photocatalyst: In-situ Bi Doping for Enhanced Photocatalytic Removal of Sulfamethoxazole (SMX) Antibiotic - Fauziyen, Sabrina Prima; Saputera, Wibawa Hendra; Sasongko, Dwiwahju (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
There is a notable emphasis on the development of photocatalysts to degrade antibiotics, such as sulfamethoxazole (SMX), in aquatic environments due to their persistence and associated toxicological impacts. In this study, BiOBr photocatalysts were synthesized by incorporating in-situ Bi doping. Various Bi/BiOBr composites were produced through a hydrothermal method at varying temperatures and subsequently characterized using X-ray diffraction (XRD), UV-vis diffuse reflectance spectroscopy (UV-vis DRS), X-ray fluorescence (XRF), and nitrogen adsorption-desorption isotherm. The characterization data revealed that the Bi-metal began to emerge at a hydrothermal temperature of 180 °C (BB180) in the BiOBr-based semiconductor and completed its conversion to Bi-metal at a hydrothermal temperature of 270 °C (BB270). This transformation leads to the generation of Bi3+ in conjunction with oxygen vacancies, acting as active electron traps and enhancing the separation efficiency of light-induced electron-hole pairs. This results in a narrow band gap of Bi/BiOBr photocatalyst, increasing its sensitivity towards visible light. BB180 exhibited the highest photocatalytic rate in the degradation of SMX with a removal efficiency of 74.35% within 4 hours of reaction under Xenon lamp irradiation and an apparent rate constant of 6.5 x 10-3 min-1, surpassing the commercial TiO2 Degussa P25. This finding opens up a new pathway for the development of a catalyst responsive to visible light, specifically designed for the detoxification of antibiotics in wastewater.